Scepticism at sea: Herman Melville and philosophical doubt - Evans, D; David Evans (2013)
This thesis explores Herman Melville’s relationship to sceptical philosophy. By reading Melville’s fictions of the 1840s and 1850s alongside the writings of Descartes, Berkeley, Hume, and Kant, I seek to show that they manifest by turns expression, rebuttal, and mitigated acceptance of philosophical doubt. Melville was an attentive reader of philosophical texts, and he refers specifically to concepts such as Berkeleyan immaterialism and the Kantian “noumenon”. But Melville does not simply dramatise pre-existing theories; rather, in works such as Mardi, Moby-Dick, and Pierre he enacts sceptical and anti-sceptical ideas through his literary strategies, demonstrating their relevance in particular regions of human experience. In so doing he makes a substantive contribution to a philosophical discourse that has often been criticised – by commentators including Samuel Johnson and Jonathan Swift – for its tendency to abstraction. Melville’s interest in scepticism might be read as part of a wider cultural response to a period of unprecedented social and political change in antebellum America, and with this in mind I compare and contrast his work with that of Dickinson, Douglass, Emerson, and Thoreau. But in many respects Melville’s distinctive and original treatment of scepticism sets him apart from his contemporaries, and in order to fully make sense of it one must range more widely through the canons of philosophy and literature. His exploration of the ethical consequences of doubt in The Piazza Tales, for example, can be seen to anticipate with remarkable precision the theories of twentieth-century thinkers such as Emmanuel Levinas and Stanley Cavell. I work chronologically though selected prose from the period 1849-1857, paying close attention to the textual effects and philosophical allusions in each work. In so doing I hope to offer fresh ways of looking at Melville’s handling of literary form and the wider shape of his career. I conclude with reflections on how Melville’s normative emphasis on the acknowledgement of epistemological limitation might inform the practice of literary criticism.